Using the concept of onomastic literacy as an analytical tool - Sofia Kotilainen (Nordisk Tidskrift för Socioonomastik)
Onomastic literacy (the skills needed to interpret the cultural and social phenomena and meanings related to name-giving) are part of a person’s cultural capital. I use this concept, which I have developed, to study personal names in family networks and in royal families in particular. This research combines the approaches and methodologies of collective biography, microhistory and the history of mentalities. The concept of onomastic literacy helps us to contextualize the lives of the research objects more closely as part of the cultures and local communities of their times, thereby revealing the deep-rooted motives behind name choices and the slow change in mentalities affecting naming.